Kewenangan Pengadilan Agama Dalam Penyelesaian Sengketa Wakaf - Cecilia Aina Putri; Mega Dewi Ambarwati (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Waqf plays a significant role in the social and economic development of the Muslim community; however, its practice often leads to disputes due to limited legal understanding, administrative irregularities, and mismanagement of waqf assets. This article examines the authority of the Religious Courts in resolving waqf disputes in Indonesia using a normative juridical method through statutory and conceptual approaches. The analysis shows that the Religious Courts have absolute authority in handling waqf disputes as regulated in Law Number 3 of 2006 and Law Number 41 of 2004, covering disputes related to the validity of waqf pledges, management, transfer, and utilization of waqf assets. However, the implementation of this authority still faces practical challenges, such as low public legal literacy, limited capacity of judges, and the suboptimal use of mediation in waqf dispute resolution. Therefore, there is a need to strengthen legal aspects, enhance human resource capacity, and increase public legal awareness regarding waqf law so that the authority of the Religious Courts in resolving waqf disputes can function effectively, fairly, and in accordance with Islamic law principles and positive law in Indonesia.